2000
DOI: 10.1200/jco.2000.18.6.1337
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine, an Oral Fluoropyrimidine Carbamate With Substantial Activity in Advanced Colorectal Cancer: Results of a Randomized Phase II Study

Abstract: Capecitabine offers a new, effective treatment option as an oral single agent in advanced CRC. Promising overall response rates were reported for all three regimens. The addition of leucovorin to the intermittent regimen had no marked effect on tumor response or median TTP. The intermittent single-agent capecitabine schedule is proposed for phase III evaluation, based on considerations of toxicity, dose-intensity, response rate, and TTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
2
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(145 citation statements)
references
References 20 publications
8
129
2
6
Order By: Relevance
“…The incidence of laboratory abnormalities was very low, despite the high incidence of bone and liver lesions. This safety profile is very similar to that seen in other clinical studies investigating capecitabine (O'Shaughnessy et al, 1998;Blum, 1999;Blum et al, 1999a,b;Aapro, 2000;Van Cutsem et al, 2000).…”
Section: Clinicalsupporting
confidence: 85%
See 1 more Smart Citation
“…The incidence of laboratory abnormalities was very low, despite the high incidence of bone and liver lesions. This safety profile is very similar to that seen in other clinical studies investigating capecitabine (O'Shaughnessy et al, 1998;Blum, 1999;Blum et al, 1999a,b;Aapro, 2000;Van Cutsem et al, 2000).…”
Section: Clinicalsupporting
confidence: 85%
“…During recruitment, data from a randomised, phase II study in colorectal cancer patients led to the selection of the intermittent capecitabine regimen for further clinical development (Van Cutsem et al, 2000), and therefore recruitment to continuous capecitabine treatment in the present study was stopped, creating a two-arm study. The recruitment target was 76 patients or 68 evaluable patients.…”
Section: Patient Demography and Dispositionmentioning
confidence: 99%
“…Nevertheless, a high incidence of severe neutropenia, associated with greater use of haematopoietic growth factors, is often reported when 5-FU, L-HOP, and CPT-11 are simultaneously combined (Falcone et al, 2002;Souglakos et al, 2002). Hand -foot syndrome, which is frequently described with the use of continuous 5-FU infusions or capecitabine (Van Cutsem et al, 2000), was never observed, possibly because the profile of frequent oral UFT/ LV dosing may resemble that of a repeated mini-bolus (Ho et al, 1998) and the UFT dose (250 m À2 day À1 ) was lower than the 300 -350 mg m À2 day À1 used by other authors. The complete absence of hand -foot syndrome is very promising and a major advantage over similar studies of capecitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not clear, as is the case with the current clinical protocols, whether prolonged exposure to UFT results in an equivalent TS inhibition rate with or without LV supplementation. On the other hand, Van Cutsem et al (2000) undertook a randomised phase II trial in advanced colorectal cancer patients aimed at selecting the most appropriate capecitabine regimen for testing in phase III studies. Two arms (2 weeks on/1 week off) differed by the presence or not of daily oral LV.…”
Section: Pharmacomodulationmentioning
confidence: 99%